Treason Medieval and Early Modern Adultery, Betrayal, and Shame - Tracy, Larissa (Brill, 2019)
"The willingness to betray one's country, one's people, one's family-to commit treason and foreswear loyalty to one entity by giving it to another-is a difficult concept for many people to comprehend. Yet, societies have grappled with treason for centuries; the motivations, implications, and consequences are rarely clear cut and are often subjective. Set against the framework of modern political concerns, Treason: Medieval and Early Modern Adultery, Betrayal, and Shame considers the various forms of treachery in a variety of sources, including literature, historical chronicles, and material culture creating a complex portrait of the development of this high crime. Larissa Tracy artfully brings together younger critics as well as seasoned scholars in a compelling and topical conversation on treason. Contributors are Frank Battaglia, Dianne Berg, Tina Marie Boyer, Albrecht Classen, Sam Claussen, Freddy C. Domínguez, Melissa Ridley Elmes, Ana Grinberg, Iain A. MacInnes, Inna Matyushina, Sally Shockro, Susan Small, Peter Sposato, Sarah J. Sprouse, Daniel Thomas, and Larissa Tracy."